Ukrainian-German paremiological parallels (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the Ukrainian-German paremiological parallels, their structural-semantic and ethno-linguistic features are cleared up. The relation between national language and culture is analyzed through interaction of lingual and ethno-cultural factors, via the influence over the language structure of everyday life, customs, rituals, beliefs, ethnic group mentality.
Keywords: paremiya; paremiological unit; equivalent; structure; semantics; ethno-linguistic features